2005
DOI: 10.1063/1.2033153
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics of TiO2 films deposited by aerosol-assisted chemical-vapor deposition from two different precursors (Ti-n-butoxide and Ti diisopropoxide)

Abstract: When titanium dioxide films are deposited by delivering a liquid aerosol of titanium-n-butoxide or titanium diisopropoxide, the crystalline and morphological features indicate that the deposition takes place through an aerosol-assisted chemical-vapor deposition (AA-CVD) process. However, the crystalline state depends on the precursor. The evidence of AA-CVD is strongly supported by the quantitative study of the growth rate rg as a function of deposition temperature. The fitting of the experimental rg curves to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
13
2
Order By: Relevance
“…These results seem to be consistent with the results obtained by Conde‐Gallardo et al . and Falaras and Xagas who both made direct comparison between TiO 2 thin films deposited by aerosol‐assisted CVD and TiO 2 thin films prepared via sol–gel technique from both TBOT and TTIP precursors.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results seem to be consistent with the results obtained by Conde‐Gallardo et al . and Falaras and Xagas who both made direct comparison between TiO 2 thin films deposited by aerosol‐assisted CVD and TiO 2 thin films prepared via sol–gel technique from both TBOT and TTIP precursors.…”
Section: Resultssupporting
confidence: 92%
“…To the best of our knowledge, no report has been published on the effects of MOCVD parameters (temperature and carrier gas flowrate) on the TiO 2 nanoparticles produced using titanium (IV) butoxide (TBOT) as the precursor, although TBOT has been proved to produce purer TiO 2 crystalline structure, with smaller and more uniform grain size than TTIP . In a previous study, we reported the effect of postdeposition heat treatment on the size, crystallinity, and photocatalytic activity of the TiO 2 nanoparticles produced via MOCVD method using TBOT precursor .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, by comparing these values with those obtained in Ref. 18 (E A ‫ס‬ 21.4 kJ/ mol), where nitrogen was used as the carrier gas, it is observed that the environment has a relatively more important influence on the activation energy. This dependence on the environment can also be observed by comparing the vertical scale of Fig.…”
Section: Resultsmentioning
confidence: 89%
“…18 Therefore, this clearly shows that we are dealing with an AA-MOCVD process and that those two phenomena must be considered as the limiting mechanisms for the film formation. In fact, by leaving B and E A as free parameters in a least-squares nonlinear regression fitting procedure, similar values are obtained for the activation energy E A ‫ס‬ 26.4 and 28.8 kJ/mol (average ∼27.6 kJ/mol) for solutions 1 and 2, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…The films studied in this work were grown by the "aerosol assisted chemical vapor deposition" technique (AA-CVD) [12], [13]. An ultrasonic generator set at 0.8 MHz, which produces droplets of 1-5 in average size, was employed to produce the aerosol to be injected in a cold wall chamber.…”
Section: Methodsmentioning
confidence: 99%